Studi Numerik Perpindahan Panas pada Tipe Shell and Tube Menggunakan CFD ANSYS di Unit PM II Indarung VI PT. Semen Padang - Khairi Habib; Arwizet K; Remon Lapisa; Andre Kurniawan (Jurnal Sains Dan Teknologi | E-ISSN : 3063-9980, 2026)
This study aims to analyze temperature distribution, the effect of oil inlet temperature variation on heat transfer effectiveness, and the performance agreement of a shell-and-tube   in the Roller Lubrication Raw Mill system of Unit PM II Indarung VI, PT Semen Padang. A quantitative approach was employed using numerical Computational Fluid Dynamics (CFD) simulation in ANSYS Fluent. The oil inlet temperature was varied at 50°C, 70°C, and 90°C, while the water inlet temperature and other operating parameters were kept constant. The simulated oil outlet temperatures were 46.74°C, 63.80°C, and 72.10°C, respectively. The   effectiveness values were 14.82%, 14.76%, and 28.87%. Validation against actual operating data resulted in relative errors of 0.24% for oil outlet temperature and 3.55% for water outlet temperature. These results indicate that the CFD model represents the operating condition of the   well. Increasing oil inlet temperature affects heat transfer rate and   effectiveness, with the highest effectiveness obtained at an oil inlet temperature of 90°C, reaching 28.87%.